Non-Invasive Methods for Estradiol Recovery from Infant Fecal Samples - Thompson, Amanda L.; Whitten, Patricia L.; Johnson, Michael L.; Lampl, Michelle L. (Frontiers in Physiology, 2010)
While the activation of the infant hypothalamic-pituitary-gonadal (HPG) axis and the existence of a postnatal gonadotrophin surge were first documented in the early 1970s, study of the longitudinal development of gonadal hormones in infancy, and the potential physiological and behavioral correlates of this development, have been hampered by reliance on infrequent serum sampling. The present study reports the validation of a noninvasive method for repeated assessment of steroid hormones in infant fecal samples. Fecal samples were collected in, and excised from cotton diaper liners, and extracted using methanol. Extracts were analyzed for estradiol using a diluted assay modification. Method validity was supported by a steroid recovery rate of at least 80%, a sensitivity of 0.35 pg/ml, and inter- and intra-assay coefficients of variations of less than 10% and 20%, respectively. Variation in estradiol concentration was assessed across (1) sample type (scraped vs. cut from diaper liner), (2) time of day (morning vs. afternoon/evening samples), (3) time interval between samples and (4) time to assay (1 day vs. 489 days after collection). Of these characteristics, only the time interval between samples within an individual was significantly associated with estradiol concentration. This is the first report of human infant fecal estradiol levels. The results support fecal recovery as a novel and powerful noninvasive tool for longitudinal studies of human infants, expanding research opportunities for investigating development of sex-specific behaviors in infancy, and the potential effects of endocrine disruptors on development.